AIDS update 2009 : - Stine, Gerald James (Prentice Hall, 1993)
This 2009 presents a balanced review of current research and information on HIV infection, HIV disease, and AIDS. AIDS UPDATE 2009 places discussion within a biological, medical, and social framework, helping readers more fully understand this devastating pandemic.